2017
DOI: 10.1021/acs.biochem.7b00098
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Loop L1 Dynamics for Substrate Capture and Catalysis in Pseudomonas aeruginosa d-Arginine Dehydrogenase

Abstract: Mobile loops located at the active site entrance in enzymes often participate in conformational changes required to shield the reaction from bulk solvent, to control the access of the substrate to the active site, and to position residues for substrate binding and catalysis. In d-arginine dehydrogenase from Pseudomonas aeruginosa (PaDADH), previous crystallographic data suggested that residues 45-47 in the FAD-binding domain and residues 50-56 in the substrate-binding domain in loop L1 could adopt two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…33 Active site lid and loop sequences are also known to facilitate substrate capture and sequestration for efficient Fl-dependent catalysis. 34,35 Closure of the active site lid of IYD is distinct from most examples since the conformational change does not accelerate an intrinsic reaction of Fl but rather switches the redox processes available to Fl. The dehalogenation activity of IYD depends on the presence of the full halotyrosine substrate.…”
Section: Switching Catalytic Specificity Of Iyd Under Control Of Subsmentioning
confidence: 99%
“…33 Active site lid and loop sequences are also known to facilitate substrate capture and sequestration for efficient Fl-dependent catalysis. 34,35 Closure of the active site lid of IYD is distinct from most examples since the conformational change does not accelerate an intrinsic reaction of Fl but rather switches the redox processes available to Fl. The dehalogenation activity of IYD depends on the presence of the full halotyrosine substrate.…”
Section: Switching Catalytic Specificity Of Iyd Under Control Of Subsmentioning
confidence: 99%
“…Loop motion and flexibility at the binding pocket play crucial roles in the optimal functions of enzymes. [8d, [9][10][11][12][13][14] Induced fluctuation by introducing appropriate mutations lead to loop movements that can reshape the binding pocket, and therefore influence substrate capture and turnover. To exploit this hypothesis in the present study, the thermostable alcohol dehydrogenase TbSADH was chosen as the model enzyme in asymmetric reduction of ketone 1 that is not accepted by the WT.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous studies have demonstrated that performing site-specific mutagenesis on either single or combined residues lining the binding pocket can efficiently affect the enantioselectivity, substrate specificity and other properties of TbSADH. [8] In recent years, there has been growing interest in the conformational dynamics of proteins, which play an important role in enzyme catalysis, and engineering of enzymes guided by conformational dynamics has become an effective strategy for protein evolution, achieving successes in expanding substrate scope, [9] increasing enantioselectivity, [10] relieving product inhibition, [11] and improving thermostability. [12] The motion of amino acid residues in loops involved in the pocket has been recognized to influence the catalytic properties of enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations